PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN DENGAN PERCEIVED VALUE SEBAGAI VARIABEL MEDIASI PADA RSUD Dr. MOEWARDI DI SURAKARTA - Wulandari, Agusti (Universitas Slamet Riyadi, 2015)
The purpose of this study was to analyze the significance of the impact of service quality on perceived value, the effect of service quality on patient satisfaction, perceived value influence on patient satisfaction, and impact of service quality on patient satisfaction mediated by perceived value. The population in this study were 100 inpatients at the Mawar 1, Mawar 2, Melati 1, Melati 2, and Melati 3 RSUD Dr Moewardi. Data collection techniques with questionnaires, observation and documentation. The sampling technique using the technique of sampling and accidental convenience. Data were analyzed using validity, reliability, classic assumption test, multiple linear analyses, t test, F test, the coefficient of determination, path analysis and test the direct effect. The results of this study showed a significant effect on the quality of service to the perceived value, quality of service to client satisfaction, perceived value to client satisfaction and perceived value mediate the quality of service to client satisfaction. Keywords: Quality of care, patient satisfaction, perceived value